2017
DOI: 10.1002/adma.201605448
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Materials for Halide Perovskite‐Based Optoelectronic Devices

Abstract: Halide perovskites have high light absorption coefficients, long charge carrier diffusion lengths, intense photoluminescence, and slow rates of non-radiative charge recombination. Thus, they are attractive photoactive materials for developing high-performance optoelectronic devices. These devices are also cheap and easy to be fabricated. To realize the optimal performances of halide perovskite-based optoelectronic devices (HPODs), perovskite photoactive layers should work effectively with other functional mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(236 citation statements)
references
References 208 publications
(290 reference statements)
3
221
1
Order By: Relevance
“…The large and well‐defined surfaces of 2D materials endow strong surface interaction with adjacent materials, which is better suited for assembly into heterosturctures. Recent investigations on heterostructures composed of 2D perovskites and conventional 2D material crystals have attracted considerable interest . Because of the large number of 2D crystals (including graphene, TMDs, metal nanosheets, etc.…”
Section: Heterostructuresmentioning
confidence: 99%
“…The large and well‐defined surfaces of 2D materials endow strong surface interaction with adjacent materials, which is better suited for assembly into heterosturctures. Recent investigations on heterostructures composed of 2D perovskites and conventional 2D material crystals have attracted considerable interest . Because of the large number of 2D crystals (including graphene, TMDs, metal nanosheets, etc.…”
Section: Heterostructuresmentioning
confidence: 99%
“…[9,10] Colloidal NCs are considered as perfect pieces of their bulk counterparts since they are normally free of non-equilibrium crystal defects. [15,16] Since NCs with different growth modes normally show different physical and chemical properties, detailed investigations on NCs growth processes may help better understand the phase transformation and the underlying growth mechanisms. [15,16] Since NCs with different growth modes normally show different physical and chemical properties, detailed investigations on NCs growth processes may help better understand the phase transformation and the underlying growth mechanisms.…”
Section: Doi: 101002/advs201802202mentioning
confidence: 99%
“…For 2D all-inorganic perovskite NPLs, Bekenstein et al first reported CsPbX 3 NPLs showing the 1–5 unit cells thickness in 2015 [141]. Since then, many efforts have been focused on synthesizing precisely tunable as well as uniform CsPbX 3 NPLs [142,143,144,145]. Currently, colloidal NPLs of perovskite metal halides have been found to be a significant family of materials for LEDs, which enriches the diversity of semiconducting nanomaterials and provide a platform for exploring new optoelectronic properties of 2D semiconducting materials.…”
Section: Approaches To Achieve Npl-ledsmentioning
confidence: 99%